Covid-19 Pandemic As An Excuse Of Non-Performance Of Contractual Obligations From Transnational Law Perspective - Elizabeth Calista Nawangsari (Jurnal sosial dan sains, 2022)
Background: The outbreak of COVID-19 has greatlyinfluenced the world’s economic situation. Its lethal potential as well as its drastic effects on international contracts, would lead to the post-pandemic litigation and arbitration questioning the applicability of the doctrines of force majeure, frustration, and hardship as an excuse of non-performances of several contractual obligations amidst the COVID-19 pandemic. Purpose: This research will discuss on the matter of the applicability of the aforementioned doctrines and its subsequent effects to excuse a non-performing party. Methods: This research uses normative juridical method with descriptive analytical approach by researching library materials and secondary data. Results: Invoking the force majeure clause requires the event to occur externally beyond the obligor’s control; the event and its consequences could not reasonably avoided or overcome by the obligor based on an external event not by their own fault. On the other hand, contracts can be frustrated under several bases, such as changes in the law, supervening illegality, outbreak of war, cancellation of an expected event, and abnormal delay outside what the parties could have reasonably contemplated at the time of contracting. While the requirements of hardship encompass the occurrence of an event for which the obligor has not assumed the risk, non-foreseeability, unavoidability and the causing by the event of a fundamental economic disequilibrium in the contract. Conclusion: To apply the doctrines of force majeure, frustration, and hardship as an excuse of non-performance of contractual obligations during an unprecedented event such as the COVID-19 outbreak, it must be assessed on a case-by-case basis of the language of the contract in light of the governing law and the circumstances of the parties’ commercial relationship.